Current management of advanced melanoma: a transformed landscape. Issue 9 (20th May 2014) - Gyorki, David E.; Spillane, John; Speakman, David; Shackleton, Mark; Henderson, Michael A.
Abstract The prognosis for patients with stage IV melanoma has historically been extremely poor and there have until recently been no effective treatment options. The last 3 years have seen a seismic shift in the management of these patients with the entry to the clinic of a number of novel agents with proven efficacy. These agents fall into two main classes: molecular‐targeted therapy and immunotherapy. Molecular therapies have primarily targeted the mitogen‐activated protein kinase pathway, most notably with oral inhibitors targetting oncogenic BRAF. Immunotherapy agents such as ipilimumab, and more recently antibodies against PD‐1 boost the host immune response against the melanoma. It is important for surgeons to be aware of these advances for a number of reasons. Firstly, to be able to inform their patients of the general options available in the event of disease progression. Secondly, these agents are currently being assessed in the adjuvant setting and are likely to demonstrate efficacy for earlier stages of disease. Finally, it is important for surgeons to be able to advocate on their patients' behalf to minimize the lag time between publication of these promising results and the availability of these agents in the clinic. Furthermore, patients with advanced melanoma should be offered participation in clinical trials in order to refine the indications for these agents to maximize their chance of benefit.